Effects of steroids on vasogenic edema due to brain tumors, a narrative review - Marzieh Shahrabi; Azin Abdollahi; Mohammad Niakan Lahiji; Tahereh Sorbi; Mohammad Solduzian (Interdisciplinary Neurosurgery)
Background and objectives: Tumor-associated edema is a serious condition that can lead to severe complications. Corticosteroids in the treatment of edema can be administered postoperatively or preoperatively. Each method has its benefits and drawbacks, and there still isn’t a consensus on choosing the best approach. In this review, the effects of different types of corticosteroids will be discussed in the management of tumor-associated edema, also it provides basis for further investigation due to the lack of data in this regard. Method: PubMed, Google Scholar, and Scopus were used for search from inception to February 13, 2025. The Scale for the Assessment of Narrative Review Article was used for evaluation and it received the score of 10. Result: Conducted search resulted in 965 relevant articles. In total, 19 of them matched to our purpose of the study. Conclusion: There are more studies focused on dexamethasone than on the other agents. Due to its lower mineralocorticoid effects, dexamethasone is usually the corticosteroid of choice, except in cases where the patient has a history of an allergic reaction to it. Preoperative administration of these medications can provide benefits, such as decreasing complications and improving the patient’s clinical status. Postoperative use of corticosteroids may also reduce the length of hospitalization.